Interactions Between Sirolimus and Anti-Inflammatory Drugs: Competitive Binding for Human Serum Albumin - Arash Khodaei; Soheila Bolandnazar; Hadi Valizadeh; Leila Hasani; Parvin Zakeri-Milani (Tabriz University of Medical Sciences, 2016)
Purpose: The aim of the present study was investigating the effects of three anti-inflammatory drugs, on Sirolimus protein biding. The binding site of Sirolimus on human serum albumin (HSA) was also determined. Methods: Six different concentrations of Sirolimus were separately exposed to HSA at pH 7.4 and 37°C. Ultrafiltration method was used for separating free drug; then free drug concentrations were measured by HPLC. Finally, Sirolimus protein binding parameters was calculated using Scatchard plots. The same processes were conducted in the presence of NSAIDs at lower concentration of albumin and different pH conditions. To characterize the binding site of Sirolimus on albumin, the free concentration of warfarin sodium and Diazepam, site I and II specific probes, bound to albumin were measured upon the addition of increasing Sirolimus concentrations. Results: Based on the obtained results presence of Diclofenac, Piroxicam and Naproxen, could significantly decrease the percentage of Sirolimus protein binding. The Binding reduction was the most in the presence of Piroxicam. Sirolimus-NSAIDs interactions were increased in higher pH values and also in lower albumin concentrations. Probe displacement study showed that Sirolimus may mainly bind to site I on albumin molecule. Conclusion: More considerations in co-administration of NSAIDs and Sirolimus is recommended.